Wahdat al-Wujûd ‘Abd al-Karîm al-Jîlî - Ghozi, Ghozi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article discusses the Islamic misticism of ?Abd al-Karîm al-Jîli which is known as wahdat al-wujûd. Al-Jîli is one of Ibn ?Arabî?s thought interpreter and commentator. In this case, al-Jîli provided Ibn ?Arabî doctrin of theosophy more shopisticated. His effort is to present Ibn ?Arabî?s doctrin more acceptable upon the frame of sharî?ah. In fact, he effort to present different angle of conception of wahdat al-wujûd. According to him wahdat al-wujûd must be seen in visioner and spiritual perspective. It is not be seen in philosophycal frame of thought as most of modern western perspective. It. In addition, wahdat al-wujûd doctrin is built on the holy experience which is based on sharî?ah.